Characterization of Hardware Impairments in Multiple Antenna Systems for DoA Estimation - Daniele Inserra; Andrea M. Tonello (Journal of Electrical and Computer Engineering)
We consider the effects introduced by hardware impairments on the estimation of the direction of arrival (DoA) deploying a multiple antenna radio system. We derive a system model from experimental measurements of a state-of-the-art hardware test bed based on an RF direct-conversion architecture. The system model includes DC offsets, carrier frequency and phase offsets, and the phase noise. Then, we propose a simple digital compensation algorithm of the impairments for bidimensional DoA estimation (azimuth and elevation) with a 3D orthogonal linear array. The robustness of the algorithm in terms of minimum-mean-squared error as a function of the hardware impairments is evaluated and compared with that achieved using the root-MUSIC algorithm.